The regulation of PSI cyclic electron transport by both plastoquinone and ferredoxin redox states: correlation with the rate of proton motive force utilization - Satoh, Hayato; Ohara, Yuri; Hanke, Guy; Ifuku, Kentaro; Shimakawa, Ginga; Suzuki, Yuji; Makino, Amane; Morigaki, Kenichi; Miyake, Chikahiro (Frontiers in Plant Science, 2025)
The capacity of plants to protect themselves from stress and efficiently assimilate CO2 depends on dynamic regulation of photosynthetic electron transport pathways. In the cyclic electron transport around photosystem I (PSI-CET), the ferredoxin (Fd) reduced by PSI donates electrons to plastoquinone (PQ), which then enter the pathway of photosynthetic linear electron transport (LET). It has been postulated that PSI-CET generates the additional proton motive force needed to drive sufficient ATP synthase activity for CO2 assimilation. The rate of PSI-CET relative to LET responds dynamically to environmental conditions and the metabolic demands of the chloroplast, but the mechanism for this regulation is still under debate. The rate of PSI-CET has been quantified as the oxidation rate of reduced Fd that exceeds the oxidation rate due to LET, which we term vFd(CET). In this study, the effects of the redox states of both PQ and Fd on vFd(CET) were analyzed in relation to the dependence of CO2 assimilation on light intensity in the C3 plant Helianthus annuus. In contrast to the rate of CO2 assimilation, the rate of PSI-CET demonstrated phases of acceleration and deceleration as the light intensity increases. The acceleration of vFd(CET) correlated with reduction state of Fd, while the deceleration correlated with reduction state of PQ. Plants grown with high nitrogen exhibited higher CO2 assimilation rates, more oxidized PQ and greater vFd(CET). Furthermore, a strong correlation was observed between vFd(CET) and the usage rate of proton motive force. These findings demonstrate that in vivo, vFd(CET) is regulated by the redox states of both Fd and PQ.